A survey on relevant Malaysian fatwā about cadaver concerning tissue engineering research - Radzi, Muhammad Aa'zamuddin Ahmad; Munirah, Sha'ban; Mohd. Azharuddin, Nur Syamimi; Azhim, Azran; Hashi, Abdurezak Abdulahi (Universiti Putra Malaysia Press, 2020)
The development of scientific knowledge in the healthcare setting shall be geared to improve the health conditions of society. Perhaps, this is one of the reasons why Muslim jurists (fuqahā`) have acknowledged the importance of biomedical practices and thus, in principle, agreed on the permissibility of its practices. However, they also raise some Islamic jurisprudence (fiqh) and ethical issues about the methods and implications of biomedical practices. Despite the great discovery of articular cartilage tissue engineering, harm and therapeutic uncertainties spark the bioethical concerns, including the use of biological samples from a cadaver in the experimental setting. The study was done by utilising the secondary analysis of local Muslim jurists’ opinions (fatwā) related to the sampling of tissue from the cadaver. The scenario of cadaveric tissue sampling can be linked to the fatwā on the issue of (1) donating cadaver for research purpose, (2) conducting post-mortem or autopsy, (3) embalming the human cadaver, and (4) donating cadaveric organs. The current fatwā has shown that honouring a human body is an essential aspect of Islamic law. Thus, researchers may need to consider other options such as obtaining the biological samples from living donor as alternatives in studying the articular cartilage regeneration.